A polymer electrolyte with heat blocking function and its preparation and application
By using polymer electrolytes composed of polymers, additives and eutectic solvents in lithium metal batteries, the polymer frame is formed at high temperatures by using the thermal response characteristics of the polymer to achieve thermal blocking function, and the balance between high-temperature safety and room temperature electrochemical properties in the prior art is solved, which significantly improves the safety and performance of the battery.
Patent Information
- Application Number
- CN202411968569.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to achieve electrolytes with good room temperature electrochemical properties and high temperature safety in lithium metal batteries.
Using a polymer electrolyte composed of polymer, additive and eutectic solvent, the thermal blocking function is achieved by cross-linking the electrolyte by the thermal response characteristics of the polymer at high temperatures.
The electrolyte has high ionic conductivity and excellent electrochemical properties at room temperature. It can cure quickly at high temperatures, cut off lithium ion transmission, terminate the battery charging and discharging process, reduce the risk of combustion and explosion, and significantly improve the safety and electrochemical properties of the secondary battery.
Smart Images

Figure BDA0005218965440000131 
Figure BDA0005218965440000141 
Figure HDA0005218965450000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary battery polymer electrolytes, and in particular relates to a polymer electrolyte with a heat blocking function and a preparation and application thereof. Background Art
[0002] The booming development of consumer electronics, electric vehicles, and energy storage stations has put forward higher requirements for battery energy density. Lithium metal has the lowest redox potential (-3.04V vs standard hydrogen electrode) and the highest specific capacity (3860mAh g -1 ), the energy density of lithium metal batteries (LMBs) using it as negative electrode material can exceed 500Wh kg -1 . However, safety issues caused by side reactions and lithium dendrite growth are important factors hindering the commercialization of LMBs. For example, dendrite growth can penetrate the separator and cause a short circuit in the battery. In addition, when LMBs work under thermal abuse conditions, a large amount of heat will be generated, which will increase the internal temperature of the battery and trigger a series of exothermic reactions, including: decomposition of the solid electrolyte membrane (SEI) on the electrode surface, interfacial side reactions, etc.; even worse, when the temperature exceeds the melting point of the polyolefin separator (165°C for polypropylene and 140°C for polyethylene), the separator will inevitably shrink, leading to severe internal short circuits and catastrophic thermal runaway. Therefore, reducing safety risks has been regarded as the top priority in the development of advanced LMBs technology.
[0003] Carbonate-based electrolytes have long been considered the culprit for battery safety issues due to their inherent flammability and poor thermal stability. In the past decade, a lot of efforts have been made to improve battery thermal safety, such as the use of solid electrolytes, functional additives, and the development of non-flammable electrolytes. Solid electrolytes have excellent thermal stability, and replacing liquid electrolytes with solid electrolytes is expected to solve the thermal safety problem of batteries. However, the poor solid-solid interface between electrodes and electrolytes is still a problem that affects charge transfer. Electrolyte modification is also a promising method to improve battery safety. For example, adding flame retardant additives, including triethyl phosphate, tributyl phosphate, and triphenyl phosphate, to liquid electrolytes is a strategy to reduce the risk of battery combustion. However, these additives are prone to side reactions at the electrode interface, which deteriorates the battery cycling stability. Developing an electrolyte with both good room temperature electrochemical performance and high temperature safety is expected to accelerate the commercialization of lithium metal batteries.
[0004] Chinese patent CN113540558A discloses a polymer electrolyte with a thermal shutdown function. The polymer electrolyte membrane contains two layers: one layer is a polymer matrix layer with a thermal shutdown function (containing a polymer matrix, an inorganic filler, a liquid electrolyte and a polymer monomer); the other layer is an ionic liquid layer (containing a polymer, a lithium salt and an ionic liquid). The electrolyte membrane cuts off ion transmission by polymerizing the polymer monomers in the first layer under thermal conditions to prevent combustion and explosion caused by thermal runaway of the battery. However, the preparation process of the polymer electrolyte membrane requires two-step casting, which is a relatively complicated process and is not suitable for industrial production.
[0005] Chinese patent CN117199715A discloses a heat-blocking diaphragm and a method for preparing the same. The diaphragm is prepared by continuous electrospinning of a spinning solution containing a base film and a polymer spinning solution. When the temperature rises to the melting point of the polymer layer, the layer structure collapses to form a non-porous dense layer, thereby blocking ion transmission and terminating the charge and discharge reaction of the battery. Since the diaphragm is prepared by electrospinning, the mechanical strength of the diaphragm is poor, so it may be pierced by growing dendrites during a long cycle, causing safety issues.
[0006] Therefore, the existing technology still has certain technical problems in studying electrolytes that have both good room temperature electrochemical performance and high temperature safety. Summary of the invention
[0007] The purpose of the present invention is to achieve high room temperature electrochemical performance and high temperature safety of the electrolyte, and to provide a polymer electrolyte with a heat blocking function and its preparation and application.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] A polymer electrolyte with a heat blocking function, the electrolyte consisting of a polymer, an additive and a low eutectic solvent.
[0010] The mass fraction of the polymer in the electrolyte is 1.5-7.0%; the mass fraction of the additive in the electrolyte is 5-15%.
[0011] The polymer With thermal response characteristics, preferably One or more of cellulose, methyl cellulose, polyethylene oxide, polytetrafluoroethylene, hydroxypropyl cellulose, poly(ethylene glycol) sorbate, carboxymethyl cellulose, carboxyethyl cellulose or poly(N-acryloyl glycolamide).
[0012] The low eutectic solvent is a mixture of an organic small molecule compound and a lithium / sodium salt; wherein the molar ratio of the organic small molecule compound to the lithium / sodium salt is 1 to 12:1.
[0013] The organic small molecule compound is selected from one or more of carbonamide, acetamide, caprolactam, N,N-dimethylsulfonamide, N,N,N',N'-tetramethylsulfonamide, succinonitrile, trioxymethylene, acrylic acid, maleic acid, and 2,2'-dithiodipyridine.
[0014] The lithium / sodium salt is one or more of lithium / sodium hexafluorophosphate, lithium / sodium bis(oxalatoborate), lithium / sodium tetrafluoroborate, lithium / sodium difluorophosphate, lithium / sodium bis(trifluoromethylsulfonyl)imide, lithium / sodium perchlorate, lithium / sodium bis(fluorosulfonyl)imide, lithium / sodium trifluoromethylsulfonate or lithium hexafluoroarsenate.
[0015] The additive is one or more of dimethyl fluorocarbonate, diethyl fluorocarbonate, ethyl methyl fluorocarbonate, difluoroethylene carbonate, fluoroethylene carbonate, fluoroboric acid ester, fluorophosphate ester, ethyl fluoroacetate, fluorocarbamate, vinylene carbonate, boron-containing additives, sulfur-containing additives, fluorinated additives, nitrile additives, anhydride additives or 1,3-propane sultone.
[0016] The room temperature ionic conductivity of the polymer electrolyte with heat blocking function is higher than 1×10 -4 S cm -1 , electrochemical window is 0~4.3V, has thermal curing ability, and the ionic conductivity after curing is less than 3×10 -6 S cm -1 .
[0017] A method for producing a polymer electrolyte with a thermal blocking function comprises the following steps:
[0018] S1, preparation of a low eutectic solvent: mixing an organic small molecule compound and a lithium / sodium salt, and stirring at room temperature until the two form a homogeneous solution to obtain a low eutectic solvent;
[0019] S2, adding additives to the low eutectic solvent of S1, stirring evenly to obtain an electrolyte;
[0020] S3, under stirring conditions, adding a polymer to the electrolyte obtained in S2, stirring to make the polymer uniformly dispersed in the solution, to obtain a polymer electrolyte with a heat blocking function.
[0021] An application of the polymer electrolyte with heat blocking function, wherein the polymer electrolyte with heat blocking function is used in an energy storage device.
[0022] The energy storage device is a lithium / sodium ion battery, a lithium / sodium metal battery and a lithium / sodium supercapacitor.
[0023] The advantages of the present invention are:
[0024] The present invention adopts a simple and convenient method to prepare a polymer electrolyte with heat blocking function. The electrolyte is prepared by adding a polymer and an additive into a low eutectic solvent. It is liquid at room temperature and has good room temperature ionic conductivity (>1×10 -4 S cm -1 ), oxidation stability potential ≥4.3V, and excellent stability to lithium; when the temperature rises, the polymer in the electrolyte is cross-linked through chemical bonds and intermolecular forces to form a polymer framework, which solidifies the electrolyte and cuts off the transmission of lithium ions, thereby realizing overheating protection of the energy storage device.
[0025] Under the condition of thermal abuse, the polymers in the electrolyte are cross-linked with each other through intermolecular hydrophobic association or chemically bonded to form a polymer framework, so that the electrolyte is rapidly solidified, and the ionic conductivity of the solidified electrolyte is significantly reduced (<3×10 -6 S cm -1 ), thereby terminating the battery charging and discharging process and preventing further heat generation; at the same time, the solidified electrolyte prevents the positive and negative electrodes of the battery from directly contacting each other, preventing the battery from thermal runaway; in addition, the excellent non-flammability can significantly reduce the risk of combustion and explosion of the battery. Therefore, the polymer electrolyte of the present invention can greatly improve the safety and electrochemical performance of secondary batteries, and is particularly suitable for energy storage devices, especially for high-safety, high-energy-density lithium / sodium ion batteries, lithium / sodium metal batteries (including lithium-sulfur batteries and sodium-sulfur batteries), dual-ion batteries, secondary batteries, and lithium / sodium supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are photos of the polymer electrolyte with heat blocking function provided in Example 1 of the present invention at room temperature and 80°C.
[0027] Figure 2 The ionic conductivity of the polymer electrolyte with heat blocking function prepared in Example 2 of the present invention is 30-70°C.
[0028] Figure 3 This is the polymer electrolyte electrochemical window with heat blocking function prepared in Example 2 of the present invention.
[0029] Figure 4 Cycling performance of a lithium iron phosphate / lithium metal battery assembled with a polymer electrolyte with heat blocking function prepared in Example 2 of the present invention at room temperature and 1C. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with embodiments:
[0031] Example 1
[0032] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium hexafluorophosphate were mixed in a molar ratio of 2:1, and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0033] S2, adding 10% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0034] S3, adding 2.5% hydroxypropyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0035] The heat curing temperature of the polymer electrolyte with heat blocking function prepared in Example 1 was tested by heating, and the state of the electrolyte at room temperature and high temperature was recorded. Figure 1 .Depend on Figure 1 It can be seen that the polymer electrolyte with heat blocking function prepared in Example 1 is liquid at room temperature, and when the temperature is higher than 80° C., the electrolyte solidifies.
[0036] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by AC impedance spectroscopy and was found to be 7.3×10 -4 S cm -1 The curing temperature is 82°C, and the ionic conductivity of the electrolyte after curing is 1.73×10 -6 S cm -1 The electrochemical window is 0-4.31V. The above polymer electrolyte with heat blocking function is assembled with lithium iron phosphate positive electrode, separator, and lithium metal negative electrode to assemble lithium iron phosphate half-cell. The cycle performance and coulombic efficiency of the battery are tested at room temperature, 2.7-4.2V, and 1C current density. The battery's first cycle discharge capacity is 147mAh g -1 , the capacity retention rate after 100 cycles is 95%.
[0037] Example 2
[0038] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a molar ratio of 2:1 and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0039] S2, adding 15% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0040] S3, adding 2% methyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0041] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the thermal blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 8.71×10 -4 S cm -1 (See Figure 2 ), the curing temperature is 80℃, and the ionic conductivity of the electrolyte after curing is 1.71×10 -6 S cm -1 , the electrochemical window is 0-4.30V (ref. Figure 3 ).
[0042] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the cell were tested at room temperature, 2.7-4.2V, and 1C current density (see Figure 4 ),Depend on Figure 4 It can be seen that the battery’s first cycle discharge capacity is 150 mAh g -1 , the capacity retention rate after 100 cycles is 96%.
[0043] Comparative Example 1
[0044] The difference from Example 2 is that methylcellulose is not added, specifically:
[0045] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a molar ratio of 2:1 and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0046] S2, adding 15% of fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring at room temperature to obtain an electrolyte.
[0047] The steel-on-steel symmetrical battery was assembled with the above electrolyte, and the room temperature ionic conductivity of the electrolyte was tested by AC impedance spectroscopy to be 9.77×10 -4 S cm -1 The electrolyte does not undergo thermal curing at high temperatures, and the ionic conductivity is 1.25×10 -3 S cm -1 .
[0048] It can be seen from the comparative example that the polymer added to the electrolyte in the embodiment of the present invention can ensure that the electrolyte undergoes hydrophobic association at high temperature to trigger electrolyte solidification and cut off ion transmission.
[0049] Comparative Example 2
[0050] The difference from Example 2 is that fluoroethylene carbonate is not added, specifically:
[0051] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a molar ratio of 2:1 and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0052] S2, add 2% methyl cellulose to the colorless deep eutectic solvent (DES) obtained in S1, stir at room temperature until dissolved, and obtain an electrolyte.
[0053] The steel-on-steel symmetrical battery was assembled with the above electrolyte, and the room temperature ionic conductivity of the electrolyte was tested by AC impedance spectroscopy to be 1.0×10 -4 S cm -1 The curing temperature is 77°C, and the ionic conductivity of the electrolyte after curing is 1.91×10 -6 S cm -1 The electrochemical window is 0-4.30V. The above electrolyte is assembled with lithium iron phosphate positive electrode, separator, and lithium metal negative electrode to assemble lithium iron phosphate half-cell. The cycle performance and coulombic efficiency of the battery are tested at room temperature, 2.7-4.2V, and 1C current density. The battery's first cycle discharge capacity is 145mAh g -1 , the capacity retention rate after 100 cycles is 56%.
[0054] From this comparative example, it can be seen that the addition of additives to the electrolyte in the embodiment of the present invention can reduce the viscosity of the system and improve the ionic conductivity on the one hand; on the other hand, it can stabilize the electrode / electrolyte interface and improve the long cycle performance.
[0055] Example 3
[0056] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed at a molar ratio of 2.5:1, and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0057] S2, adding 20% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0058] S3, under stirring conditions, add 5% poly (N-acryloyl glycolamide) to the solution obtained in S2, and stir at warm temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0059] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 1.32×10 -3 S cm -1 The curing temperature is 125°C, and the ionic conductivity of the electrolyte after curing is 1.93×10 -6 S cm-1 ,, the electrochemical window is 0-4.32V.
[0060] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode. The cycling performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery had a first-cycle discharge capacity of 153mAh g -1 , the capacity retention rate after 100 cycles is 97%.
[0061] Example 4
[0062] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a molar ratio of 2:1 and stirred at room temperature for 10 hours to obtain a colorless deep eutectic solvent (DES);
[0063] S2, adding 15% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0064] S3, adding 4% poly(N-acryloyl glycolamide) to the solution obtained in S2 under stirring conditions, stirring at room temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0065] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 1.12×10 -3 S cm -1 The curing temperature is 120°C, and the ionic conductivity of the electrolyte after curing is 2.01×10 -6 S cm -1 , the electrochemical window is 0-4.32V.
[0066] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode. The cycling performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery had a first-cycle discharge capacity of 156mAh g -1 , the capacity retention rate after 100 cycles is 95%.
[0067] Example 5
[0068] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a molar ratio of 2:1 and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0069] S2, adding 15% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0070] S3, under stirring conditions, adding 3% poly (N-acryloyl glycolamide) to the solution obtained in S2, and stirring at room temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0071] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 1.05×10 -3 S cm -1 The curing temperature is 118°C, and the ionic conductivity of the electrolyte after curing is 2.90×10 -6 S cm -1 , the electrochemical window is 0-4.31V.
[0072] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode. The cycling performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 150mAh g -1 , the capacity retention rate after 100 cycles is 96%.
[0073] Example 6
[0074] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and sodium bis(fluorosulfonyl)imide (NaFSI) were mixed in a molar ratio of 2:1 and stirred at room temperature for 10 hours to obtain a colorless deep eutectic solvent (DES);
[0075] S2, adding 10% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0076] S3, under stirring conditions, add 2% methyl cellulose to the solution obtained in S2, and stir at room temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0077] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 1.31×10 -3 S cm -1 The curing temperature is 105°C, and the ionic conductivity of the electrolyte after curing is 2.37×10 -6 S cm -1 , the electrochemical window is 0-4.30V.
[0078] The above-mentioned polymer electrolyte with heat blocking function was assembled into a sodium ion battery with sodium vanadium phosphate positive electrode, separator and hard carbon negative electrode. The cycle performance and coulombic efficiency of the battery were tested at room temperature, 1.0-4.0V and 1C current density. The results showed that the battery had a first-cycle discharge capacity of 123mAh g -1 , the capacity retention rate after 100 cycles is 96%.
[0079] Example 7
[0080] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) were mixed in a molar ratio of 2:1 and stirred at room temperature for 10 hours to obtain a colorless deep eutectic solvent (DES);
[0081] S2, adding 5% of ethylene difluorocarbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0082] S3, under stirring conditions, add 2% methyl cellulose to the solution obtained in S2, and stir at room temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0083] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 6.75×10 -4 S cm -1 The curing temperature is 130°C, and the ionic conductivity of the electrolyte after curing is 1.97×10 -6 S cm -1 , the electrochemical window is 0-4.36V.
[0084] The above polymer electrolyte with heat blocking function was assembled into a sodium ion battery with sodium vanadium phosphate positive electrode, separator, and hard carbon negative electrode, and the battery's cycle performance and coulombic efficiency were tested at room temperature, 1.0-4.0V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 120mAh g -1 , the capacity retention rate after 200 cycles is 94%.
[0085] Example 8
[0086] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium hexafluorophosphate (LiPF6) were mixed in a molar ratio of 2:1, and stirred at room temperature for 10 hours to obtain a colorless deep eutectic solvent (DES);
[0087] S2, adding 15% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0088] S3, under stirring conditions, add 5% polytetrafluoroethylene to the solution obtained in S2, and stir at room temperature until dissolved to obtain a polymer electrolyte with heat blocking function.
[0089] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the thermal blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 5.81×10 -4 S cm -1 The ionic conductivity after curing is 2.03×10 -6 S cm -1 The curing temperature is 107°C and the electrochemical window is 0-4.35V.
[0090] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 144mAh g -1 , the capacity retention rate after 200 cycles is 92%.
[0091] Example 9
[0092] S1, preparation of a deep eutectic solvent: N,N,N',N'-tetramethylsulfonamide and lithium bis(fluorosulfonyl)imide (LiFSI) were mixed in a molar ratio of 2:1, and stirred at room temperature for 10 hours to obtain a colorless deep eutectic solvent (DES);
[0093] S2, adding 15% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0094] S3, under stirring conditions, add 3% polytetrafluoroethylene to the solution obtained in S2, and stir at room temperature until dissolved to obtain a polymer electrolyte with heat blocking function.
[0095] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 6.63×10 -4 S cm -1 The curing temperature is 125℃, and the ionic conductivity after curing is 2.74×10 -6 S cm -1 The electrochemical window is 0-4.35V.
[0096] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode. The cycling performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery had a first-cycle discharge capacity of 149mAh g -1, the capacity retention rate after 200 cycles is 95%.
[0097] Example 10
[0098] S1, preparation of a deep eutectic solvent: succinonitrile and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a molar ratio of 10:1 and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0099] S2, adding 9% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0100] S3, adding 2% hydroxypropyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0101] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the thermal blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was found to be 9.13×10 -4 S cm -1 The curing temperature is 89°C, and the ionic conductivity after curing is 2.81×10 -6 S cm -1 , the electrochemical window is 0-4.45V.
[0102] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 155mAh g -1 , the capacity retention rate after 200 cycles is 91%.
[0103] Embodiment 11
[0104] S1, preparation of a deep eutectic solvent: succinonitrile and lithium bis(trifluoromethylsulfonyl)imide were mixed in a molar ratio of 8:1, and stirred at room temperature for 10 hours to obtain a colorless deep eutectic solvent (DES);
[0105] S2, add 10% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stir evenly;
[0106] S3, adding 1.5% hydroxypropyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved, thereby obtaining a polymer electrolyte with heat blocking function.
[0107] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was found to be 7.33×10 -4 S cm -1 The curing temperature is 91°C, and the ionic conductivity after curing is 2.73×10 -6 S cm -1 , the electrochemical window is 0-4.47V.
[0108] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 153mAh g -1 , the capacity retention rate after 200 cycles is 94%.
[0109] Example 12
[0110] S1, preparation of a deep eutectic solvent: succinonitrile and lithium bis(trifluoromethylsulfonyl)imide were mixed in a molar ratio of 6:1, and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0111] S2, adding 15% fluoroethylene carbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0112] S3, adding 2.5% hydroxypropyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved to obtain a polymer electrolyte with heat blocking function.
[0113] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the thermal blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was found to be 7.13×10 -4 S cm -1 The curing temperature is 79°C and the ionic conductivity after curing is 2.69×10 -6 S cm -1 , the electrochemical window is 0-4.50V.
[0114] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 151mAh g -1 , the capacity retention rate after 200 cycles is 94%.
[0115] Embodiment 13
[0116] S1, preparation of a deep eutectic solvent: succinonitrile and lithium bis(trifluoromethylsulfonyl)imide were mixed in a molar ratio of 5:1, and stirred at room temperature for 10 hours to obtain a colorless deep eutectic solvent (DES);
[0117] S2, adding 5% of ethylene difluorocarbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0118] S3, adding 2% hydroxypropyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved to obtain a polymer electrolyte with heat blocking function.
[0119] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the heat blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 7.12×10 -4 S cm -1 The curing temperature is 83°C, and the ionic conductivity after curing is 2.74×10 -6 S cm -1 , the electrochemical window is 0-4.53V.
[0120] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 149mAh g -1 , the capacity retention rate after 200 cycles is 94%.
[0121] Embodiment 14
[0122] S1, preparation of a deep eutectic solvent: succinonitrile and lithium bis(trifluoromethylsulfonyl)imide were mixed in a molar ratio of 4:1, and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0123] S2, adding 10% of ethylene difluorocarbonate to the colorless deep eutectic solvent (DES) obtained in S1, and stirring evenly;
[0124] S3, adding 1.5% hydroxypropyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved to obtain a polymer electrolyte with heat blocking function.
[0125] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the thermal blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 8.22×10 -4 S cm -1 The curing temperature is 93°C, and the ionic conductivity after curing is 2.55×10 -6 S cm -1, the electrochemical window is 0-4.88V.
[0126] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 147mAh g -1 , the capacity retention rate after 100 cycles is 97%.
[0127] Embodiment 15
[0128] S1, preparation of a deep eutectic solvent: succinonitrile and lithium bis(trifluoromethylsulfonyl)imide were mixed in a molar ratio of 10:1, and stirred at room temperature for 10 hours to obtain a colorless deep eutectic solvent (DES);
[0129] S2, add 10% ethyl fluoroacetate to the colorless deep eutectic solvent (DES) obtained in S1, and stir evenly;
[0130] S3, adding 2% hydroxypropyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved to obtain a polymer electrolyte with heat blocking function.
[0131] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the thermal blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 4.18×10 -4 S cm -1 The curing temperature is 85°C, and the ionic conductivity after curing is 2.12×10 -6 S cm -1 , the electrochemical window is 0-4.58V.
[0132] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 146mAh g -1 , the capacity retention rate after 100 cycles is 96%.
[0133] Example 16
[0134] S1, preparation of a low eutectic solvent: succinonitrile and lithium bis(trifluoromethylsulfonyl)imide were mixed in a molar ratio of 10:1, and stirred at room temperature for 12 hours to obtain a colorless deep eutectic solvent (DES);
[0135] S2, add 3% ethyl fluoroacetate to the colorless deep eutectic solvent (DES) obtained in S1, and stir evenly;
[0136] S3, adding 2% hydroxypropyl cellulose to the solution obtained in S2 under stirring conditions, and stirring at room temperature until dissolved to obtain a polymer electrolyte with heat blocking function.
[0137] The steel-on-steel symmetrical battery was assembled with the polymer electrolyte having the thermal blocking function. The room temperature ionic conductivity of the electrolyte was tested by the AC impedance spectroscopy and was 4.18×10 -4 S cm -1 The curing temperature is 92°C, and the ionic conductivity after curing is 2.47×10 -6 S cm -1 , the electrochemical window is 0-4.88V.
[0138] The polymer electrolyte with heat blocking function was assembled into a lithium iron phosphate half-cell with a lithium iron phosphate positive electrode, a separator, and a lithium metal negative electrode, and the cycle performance and coulombic efficiency of the battery were tested at room temperature, 2.7-4.2V, and 1C current density. The results showed that the battery's first cycle discharge capacity was 152mAh g -1 , the capacity retention rate after 200 cycles is 94%.
[0139] Table 1 Polymer electrolyte components with heat blocking function of Examples and Comparative Examples
[0140]
[0141]
[0142] It can be seen from the comparative examples and embodiments in Table 1 that the electrolyte prepared by mixing the polymer, lithium / sodium salt, additive, and deep eutectic solvent in specific amounts in the embodiments of the present invention has a conductivity of >1×10 -4 S cm -1 The ionic conductivity of the electrolyte is 9.77×10 -4 S cm -1 The electrolyte does not undergo thermal curing at high temperatures, and the ionic conductivity is 1.25×10 -3 S cm -1, it can be seen that the polymer added to the electrolyte of the present invention can ensure that the electrolyte undergoes hydrophobic association at high temperature to induce electrolyte solidification and cut off ion transmission. As can be seen from Comparative Example 2, due to the absence of additives, the capacity retention rate of the battery after 100 cycles is only 56%, which is significantly lower than 96% of the embodiment. It can be seen that the addition of additives to the electrolyte of the present invention can reduce the viscosity of the system and improve the ionic conductivity on the one hand; on the other hand, it can stabilize the electrode / electrolyte interface and improve the long cycle performance. Therefore, the mutual cooperation of the polymer, additive, and low eutectic solvent of the present invention enables the electrolyte to have a thermal blocking function, and at the same time can significantly reduce the combustion and explosion risks of the battery, improve the safety and electrochemical performance of the secondary battery, wherein the role of the polymer is to crosslink or polymerize at high temperature, so that the electrolyte solidifies and cuts off ion transmission; the role of the low eutectic solvent is to form a fast ion transmission channel; the role of the additive is to form a stable solid electrolyte interface layer (SEI) on the electrode surface, reduce the interface side reaction, and improve the long cycle stability of the battery. The synergistic effect of each component achieves high ionic conductivity at room temperature, excellent lithium stability, and thermal safety at high temperature, wherein the absence of any component cannot achieve the corresponding technical effect.
Claims
1. A polymer electrolyte with heat blocking function, characterized in that: The electrolyte consists of a polymer, an additive and a low eutectic solvent.
2. The polymer electrolyte with heat blocking function according to claim 1, characterized in that: The mass fraction of the polymer in the electrolyte is 1.5-7%; the mass fraction of the additive in the electrolyte is 5-15%.
3. The polymer electrolyte with heat blocking function according to claim 1, characterized in that: The polymer is one or more of cellulose, methyl cellulose, polyethylene oxide, polytetrafluoroethylene, hydroxypropyl cellulose, poly(ethylene glycol) sorbate, carboxymethyl cellulose, carboxyethyl cellulose or poly(N-acryloyl glycolamide).
4. The polymer electrolyte with heat blocking function according to claim 1, characterized in that: The low eutectic solvent is a mixture of an organic small molecule compound and a lithium / sodium salt; wherein the molar ratio of the organic small molecule compound to the lithium / sodium salt is 1 to 12:
1.
5. The polymer electrolyte with heat blocking function according to claim 4, characterized in that: The organic small molecule compound is one or more of carbonamide, acetamide, caprolactam, N,N-dimethylsulfonamide, N,N,N',N'-tetramethylsulfonamide, succinonitrile, trioxymethylene, acrylic acid, maleic acid, and 2,2'-dithiodipyridine.
6. The polymer electrolyte with heat blocking function according to claim 4, characterized in that: The lithium / sodium salt is one or more of lithium / sodium hexafluorophosphate, lithium / sodium bis(oxalatoborate), lithium / sodium tetrafluoroborate, lithium / sodium difluorophosphate, lithium / sodium bis(trifluoromethylsulfonyl)imide, lithium / sodium perchlorate, lithium / sodium bis(fluorosulfonyl)imide, lithium / sodium trifluoromethylsulfonate or lithium hexafluoroarsenate.
7. The polymer electrolyte with heat blocking function according to claim 1, characterized in that: The additive is one or more of dimethyl fluorocarbonate, diethyl fluorocarbonate, ethyl methyl fluorocarbonate, difluoroethylene carbonate, fluoroethylene carbonate, fluoroboric acid ester, fluorophosphate ester, ethyl fluoroacetate, fluorocarbamate, vinylene carbonate, boron-containing additives, sulfur-containing additives, fluorinated additives, nitrile additives, anhydride additives or 1,3-propane sultone.
8. A method for preparing a polymer electrolyte with heat blocking function according to claim 1, characterized in that: The preparation method comprises the following steps: S1, preparation of deep eutectic solvent: mixing small organic molecules with lithium / sodium salt and stirring until a homogeneous solution is formed; S2, adding additives to the homogeneous solution obtained in S1 and stirring evenly; S3, adding a polymer to the solution obtained in S2 under stirring conditions, and stirring until dissolved, thereby obtaining a polymer electrolyte with a heat blocking function.
9. An application of the polymer electrolyte with heat blocking function as claimed in claim 1, characterized in that: The polymer electrolyte with heat blocking function is used in energy storage devices.
10. The use according to claim 9, characterized in that: The energy storage device is a lithium / sodium ion battery, a lithium / sodium metal battery or a lithium / sodium supercapacitor.
Citation Information
Patent Citations
Flame-retardant polymer electrolyte with thermal shutdown function and preparation method of flame-retardant polymer electrolyte
CN113540558A
Heat blocking diaphragm, preparation method thereof and secondary battery
CN117199715A